Hybrid energy sources status of Pakistan: An optimal technical proposal to solve the power crises issues. (April 2019) - Baloch, Mazhar Hussain; Tahir Chauhdary, Sohaib; Ishak, Dahaman; Kaloi, Ghulam Sarwar; Nadeem, Muhammad Haroon; Wattoo, Waqas Ahmad; Younas, Talha; Hamid, Haris Tahir
Abstract: Power outage owing to shortage of power generation, transmission losses, lack of planning and inappropriate policies has led to escalate the energy crisis in Pakistan. The reason for selecting Pakistan is to facilitate its 220 million population and to attract the international investors to take benefit by integrating power generation units into National Grid of Pakistan (NGOP). Domestic, Industrial, health and education sectors are badly affected due to this power crisis. Instead of remedial measures and providing incentives to the investors in power sector, the government of Pakistan (GOP) has remained unable to overcome the dilemma in power sector due to improper check and balance. The failures in completion of hydropower dams and generating electricity by fossil fuels has resulted in increased power generation cost and environmental hazards. Therefore, some suitable solutions are compulsory for meeting the escalating power demands adequately. The incorporation of renewable energy units and stopping electricity theft can be the most explicit choice for meeting aforementioned problems. This paper explores the vast potential of Pakistan with respect to energy production by means of solar and wind power units. Moreover, most appropriate sites for incorporating power generation units are also critically reviewed. The paper also proposes the short-term, mid-term and long-term effective solutions along various practical proposals for overcoming the existing power crisis in Pakistan. Highlights: Severe energy crisis is observed in Pakistan due to which 220 million population and various investors are effective badly. Global trend is to switch from fossil fuels to renewable energy for healthier environment. This paper conducts a comprehensive analysis of the already existed renewable energy sources. Authors have proposed various solutions to enhance the productivity of already existed resources. Long term, mid-term and short terms solutions have been proposed to overcome the energy crisis in developing countries.